Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve using gauss-Jordan elimination

X1 - 3x2 = -5
-3x1 - x2 = 5

Sagot :

[tex]\begin{cases}x_1&-3x_2=-5\\-3x_1&-x_2=5\end{cases}\\\begin{cases}3x_1&-9x_2=-15\\-3x_1&-x_2=5\end{cases}\\\begin{cases}&-10x_2=-10\\-3x_1&-x_2=5\end{cases}\\\begin{cases}&x_2=1\\-3x_1&-1=5\end{cases}\\\boxed{\begin{cases}x_2=1\\x_1=-2\end{cases}}[/tex]